ANALISIS STRUKTUR DAN MAKNA CERITA ANAK SABALAH DAN ARUM BERISTRI TUAN BUNGSU ANAK RAJA (SASTRA LISAN DAYAK KANAYATN) - Priyadi, Antonius Totok; Khairullah, Khairullah; Elofhia, Loriya; Annisa, Ayu; Sabila, Lisa (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This research examines two Dayak Kanayatn folktales from Landak Regency, West Kalimantan, namely “Anak Sabalah” and “Arum Beristri Tuan Bungsu Anak Raja”. The purpose of this research is to find the storytelling environment, structure, and meaning of the story of "Anak Sabalah" and to find the storytelling environment, structure, and meaning of the story of "Arum Beristri Tuan Bungsu Anak Raja", the Dayak folklore of Kanayatn. Using a descriptive qualitative approach, the study focuses on the storytelling environment, structure, and meaning of the tales. Data were gathered through document analysis and interviews, then validated by prolonged observation, triangulation, and referential adequacy. The results show that the stories are conveyed through narrative and dialogue in a traditional community, highlighting changes in character functions due to broken promises and the predominance of goodness that ultimately prevails. The meanings of the two tales involve humans relationship with God (faith in Jubata and destiny), with others (mutual giving and deliberation), with oneself (determination, humility, courage), and with nature (mutual dependence). Based on these findings, it is recommended to preserve the folktales, utilize local wisdom in regional policy-making, and incorporate them as teaching material for fantasy (folktale) texts in seventh-grade junior high school classes.